Testing the application of corrective adjustment procedures for removal of relative age effects in female youth swimming. Issue 10 (18th May 2020) - Abbott, Shaun; Moulds, Kylie; Salter, James; Romann, Michael; Edwards, Lucy; Cobley, Stephen
ABSTRACT: The purpose of this study was (1) accurately estimate longitudinal relationships between decimal age (i.e., chronological and relative) and performance in Australian female 100 m (N = 765) and 200 m (N = 428) Breaststroke swimmers (10–18 years); and (2) determine whether corrective adjustment procedures could remove Relative Age Effects (RAEs) in an independent sample of age-matched 100 m (N = 2, 491) and 200 m (N = 1, 698) state/national level Breaststroke swimmers. In Part 1, growth curve modelling quantified longitudinal relationships between decimal age and swimming performance. In Part 2, relative age distributions (Quartile 1–4) for "All", "Top 25%" and "10%" of swimming times were examined based on raw and correctively adjusted swim times for age-groups. Based on raw swim times, finding identified RAE effect sizes increased in magnitude (small-medium) with selection level ("All"-"Top 25%") in 12–14 years age-groups for both events. However, when correctively adjusted swim performances were examined, RAEs were primarily absent across all age-groups and selection levels. Using longitudinal reference data, corrective adjustment procedures removed relative age advantages in female youth Breaststroke performance. Removing the influence of relative age-related differences is predicted to improve the accuracy of identifying genuinely skilled youth swimmers.